Staging Civilization : A Transnational History of French Theater in Eighteenth-Century Europe - Markovits, Rahul, 1981- (Book collections on Project MUSE., 2021)
"By examining the presence of French companies of actors in a wide set of courts and cities throughout Europe, this book uncovers the complex mechanisms underpinning the dissemination of French culture during the long eighteenth century"--